Expectations of Aging as Gendered Political Discourse in 19th-century France - Davis, Stacey Renee (Enfances, Familles, Générations, 2017)
Research framework: In 1881 the French Third Republic allocated yearly pensions to nearly 25,000 elderly citizens as reparations for political oppression suffered thirty years earlier during the previous regime. To receive a pension, each former political prisoner ( proscrit ), their widows or children, wrote letters describing their punishment and the wider multi-generational impact of that oppression.Objectives: This article uncovers understandings shared by Republican administrators and a particular group of their staunch working-class supporters - artisans, rural laborers, and small-town shopkeepers - of the definitions of old age, expectations for life trajectories, and how gender affected both expectations and experiences.Methodology: Historical, qualitative analysis of archival documents at the French National Archives and departments of the Ain, Allier, Drôme, Hérault, Rhône, Saône-et-Loire, Vaucluse and Yonne, France.Results: Analysis demonstrates pension applicants drew upon common understandings of gender and age-based roles to strengthen their claims to pensions both as erstwhile heroes of the newly democratic regime and as members of an indigent, elderly poor worthy of government aid.Conclusions: Former proscrits , their families and Republican administrators shared assumptions about the definition of the onset of old age as linked to gender; about expectations that elderly men would work indefinitely in old age until physically unable to do so but that the specter of elderly working women was shameful and a blot on Republican values; and about an understanding that pensions allowed a dignified old-age for both male and female applicants by undoing dangerous shifts in gender roles perceived as triggered by the political oppression decades earlier.Contribution: The article contributes to scholarship on changing European understandings of the gendered dimensions of old age in the late 19th century, just before decades of social welfare legislation.